"Armed with faith": church membership, Pentecostal beliefs and migrant belonging in Harare, Zimbabwe. Issue 3 (3rd July 2022) - Mushonga, Rufaro Hamish
Abstract : This ethnographic study explores how church membership and Pentecostal beliefs afford Nigerian migrant traders living in Harare an opportunity to embed themselves within the spaces of Harare's Downtown informal settlement, which are characterised by entrenched and heightened forms of exclusion and hostility. Their church membership and Pentecostal beliefs enable them to gain a voice, negotiate place and space, and align themselves flexibly with their hosts. Displacement and migration have been explored in the Zimbabwean context, but the focus has been on Zimbabweans as migrants to surrounding countries. Whilst internal displacement has received some attention, not much has been given to the experiences of migrants from other African countries in Zimbabwe. This article addresses this omission by documenting how the church membership and Pentecostal beliefs of Nigerian migrants allow them to map a symbolic landscape and construct a symbolic dwelling amidst heightened forms of exclusion.